1994
DOI: 10.1002/art.1790070306
|View full text |Cite
|
Sign up to set email alerts
|

Weather, beliefs about weather, and disease severity among patients with fibromyalgia

Abstract: Objective. This investigation 1) examined the relationships among actual weather, disease severity, and symptoms for individuals with fibromyalgia, 2) assessed subjects' beliefs about weather affecting their symptoms, and 3) examined differences between individuals with high and low “weather sensitivity.” Methods. Eighty‐four individuals meeting Yunus' criteria for the diagnosis of fibromyalgia participated. Subjects completed the Weather and Pain Questionnaire (WPQ), the Arthritis Impact Measurement Scales (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 13 publications
1
27
0
1
Order By: Relevance
“…10 31 Weather sensitivity has been associated with the personality characteristics of the patient. 7 Personality as a factor in FM http://ard.bmj.com/ pain is uncertain, although high levels of neuroticism are often associated with symptoms of depression and anxiety. Anxiety and depression are associated with the reporting of greater subjective pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 31 Weather sensitivity has been associated with the personality characteristics of the patient. 7 Personality as a factor in FM http://ard.bmj.com/ pain is uncertain, although high levels of neuroticism are often associated with symptoms of depression and anxiety. Anxiety and depression are associated with the reporting of greater subjective pain.…”
Section: Discussionmentioning
confidence: 99%
“…9 Hagglund et al reported that most patients with fibromyalgia believe that weather affects their symptoms, and noted a strong relationship between patients' weather beliefs and self reported pain scores. 7 The aim of this study was to evaluate the relationship between the daily weather and pain variations in patients with FM. We focused upon the commonly used weather parameters (barometric pressure, cloudiness, wind speed, relative humidity, temperature, and sunlight).…”
mentioning
confidence: 99%
“…Pain symptoms may be modulated by various factors including psychological stress, excessive physical activity, fatigue, or changes in the weather [24]. Some patients also report a superficial burning quality to pain with increased sensitivity to painful stimuli-termed hyperalgesia, and may also have features of allodynia or pain following an innocuous stimulation such as touch [25].…”
Section: Methodsmentioning
confidence: 99%
“…There are a number of studies concerning WS related to conditions such as chronic pain (Jamison et al 1995;Shutty et al 1992), rheumatoid arthritis (Gorin et al 1999;Drane et al 1997;Hagglund et al 1994) or psychological impairments (Vadzyuk and Mikula 1997;Faust and Hole 1972). Some of these studies have demonstrated a relationship between weather conditions and the occurrence of industrial and car accidents, excluding trivial reasons such as icy ground or storms (Rauschhofer et al 1981;Jendritzky et al 1978).…”
Section: Introductionmentioning
confidence: 98%